Influence of plant extract and edible coatings on quality of nectarine (Prunus persica) fruits - A, SOWMYASHREE; SHARMA, R R; RUDRA, SHALINI G; VERMA, M K; GROVER, MINAKSHI (The Indian Journal of Agricultural Sciences, 2021)
A study was carried out on the influence of plant extract and edible coating on nectarine fruits during 2019-20 at ICAR-IARI, New Delhi. We attempted the use of different hydrocolloid-based coatings like carboxy methylcellulose (CMC) and chitosan (CH) alone and in combination with mixed plant extract (MPE) of moringa, eucalyptus and marigold on Snow Queen nectarine fruits. Fruits were coated with these coatings and stored at supermarket conditions (18 ± 2ºC and 85-90% RH) for 16 days. During storage, observations on weight loss, fruit firmness, quality attributes and sensory evaluation were recorded at 4 days interval. The results revealed that the weight loss (WL) and fruit firmness decreased with the increase in storage period, and fruits coated with layer-by-layer coatings of CMC-CHMPE exhibited the highest lowest WL and highest fruit firmness at the end of storage. The total soluble solids (TSS) and ascorbic acid content increased up to some period, and then these attributes showed declining trend. In all, layerby- layer coating of CMC-CH-MPE was the best treatment for reducing WL, maintaining fruit firmness and quality of Snow Queen up to 16 days of storage at supermarket conditions.